Teriflunomide for multiple sclerosis in real‐world setting. (20th March 2017) - Elkjaer, M. L.; Molnar, T.; Illes, Z.
Abstract : Objectives: Teriflunomide 14 mg is a once‐daily oral disease‐modifying treatment for relapsing‐remitting multiple sclerosis. We examined adverse event (AE) profile and efficacy in real life. Materials and methods: In this observational cohort study, we retrospectively examined 1521 blood samples and data of 102 patients followed for up to 28 months. Results: The number of female patients starting teriflunomide peaked in the fifth decade, 10 years later compared to male patients ( P <.001), reflecting pregnancy concerns. Seventy‐six percentages of patients shifted to teriflunomide from treatment with interferon‐beta. Expanded disability status scale improved in 11% of patients (18.2±3.6 months follow‐up) and remained constant in 67.5% (15±5.3 months follow‐up). Of ten relapses, three occurred within 6 months after starting treatment. Seventeen patients (16.5%) discontinued teriflunomide: 53% because of AEs and 29% because of relapse. Levels of alanine aminotransferase (ALT) remained normal in 95.3% of the blood samples and remained below 1.5 times the upper limit of normal in 91% of the 4.7% abnormal samples. One‐third of the patients had abnormal ALT values at least once. Haematological abnormalities were found in <4% of the blood samples, but at least one abnormal value was observed in up to 21% of the patients. Conclusions: Efficacy and safety of teriflunomide in real‐life setting support data obtained by the pivotal trials. Laboratory abnormalities are rare among the large number of samples, but patients may commonly have a single mild, abnormal value if frequently tested.